Aid effectiveness in Ghana: How’s the L’Aquila food security initiative doing? - Benin, Samuel; Makombe, Tsitsi; Johnson, Michael E. (International Food Policy Research Institute, 2014)
This paper assesses the degree to which the L’Aquila Food Security Initiative (AFSI) has been implemented in Ghana within the framework of managing for development results (MfDR), and to evaluate progress in various outcomes, including economic governance, agricultural growth, poverty, and food and nutrition security. The MfDR approach, which has gained widespread support globally for obtaining results, is endorsed by the government of Ghana and reflected in the Ghana Aid Policy and Strategy.